The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/anie.201711390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Chiral Ketones and Chiral Alkanes Using Radical Polar Crossover Reactions of Vinyl Boron Ate Complexes

Abstract: Vinyl boron ate complexes of enantioenriched secondary alkyl pinacolboronic esters undergo stereospecific radical‐induced 1,2‐migration in radical polar crossover reactions. In this three‐component process various commercially available alkyl iodides act as radical precursors and light is used for chain initiation. Subsequent oxidation and protodeborylation leads to valuable α‐chiral ketones and chiral alkanes, respectively, with excellent enantiopurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Based on this assumption, we decided to investigate the reactivity of alkenylboron ate complexes as radical trap in order to develop a three-component reaction involving a radical addition to a vinylboron ate complex followed by a halogen transfer and a final [1,2]-metalate rearrangement (Scheme 1, c). At an advanced stage of our study, Studer, [23][24] Aggarwal [25][26] and Morken [27] reported very closely related transformations. We report here a single-pot approach involving neither solvent switch nor the use of any additive (photoredox catalyst or cosolvent…”
Section: Introductionmentioning
confidence: 70%
“…Based on this assumption, we decided to investigate the reactivity of alkenylboron ate complexes as radical trap in order to develop a three-component reaction involving a radical addition to a vinylboron ate complex followed by a halogen transfer and a final [1,2]-metalate rearrangement (Scheme 1, c). At an advanced stage of our study, Studer, [23][24] Aggarwal [25][26] and Morken [27] reported very closely related transformations. We report here a single-pot approach involving neither solvent switch nor the use of any additive (photoredox catalyst or cosolvent…”
Section: Introductionmentioning
confidence: 70%
“…[121] Denmark et al have recentlyp ublished ar eport on the transition-metal-free enantioselective carbosulfenylation of alkenyl boronates to afford b-sulfur secondaryo rt ertiary alcohols after oxidation (Scheme 28c). [122] The aforementioned substrates, tetracoordinated alkenyl boronate complexes, have also been employed in radical chemistry.S tuder et al [123] and Aggarwal et al, [124] independently,a nd later Renaud and co-workers, [125] have shown that the vinyl boronate complexes are efficient radical acceptors, and the radicala nion adducts undergo 1,2-alkyl/aryl shifts from boron to carbon,t hus leading to av ariety of synthetically useful products (Scheme 29a). This method has been applied by Aggarwal's group with heterocycles such as furan or indole to give 2,5-disubstituted furanso r2 ,3-disubstituted indoles (Scheme29b).…”
Section: Applications Of Alkenyl Boronatesmentioning
confidence: 99%
“…2 Oxidation of such boronic esters using basic H2O2 to give the corresponding alcohol is widely used (Scheme 1), 3 including in the synthesis of complex natural products. 4 If access to the carbonyl in one step is desired, 5 oxidation of either an alkenyl-or -heteroatom-substituted alkylboron is required. However, respectively these reagents are susceptible to protodeboronation and are often non-trivial to prepare.…”
Section: Takedownmentioning
confidence: 99%